VALORISATION OF PLANT BIOMASS FOR KALAMKARI OF ANDHRA PRADESH: WASTE DISPOSAL ISSUES - SRIVANI THADEPALLI; SUNDERVEL AMSAMANI (The Journal of Research ANGRAU, 2025)
Indian crafts utilize indigenous materials known for their sustainability and biodegradability. A craft diagnostic survey conducted in 2023 at the Machilipatnam Kalamkari cluster in Andhra Pradesh revealed improper disposal of organic waste from production processes, posing environmental and health risks. Analysis of gross calorific value (GCV), ash content, moisture content, fixed carbon, and volatile matter showed that the GCV of bio-waste samples ranged from 3848 to 4143 Kcal/kg, surpassing that of cow dung and matching or exceeding Indian coal (4050 K. Cal/Kg) and lignite (3200 K. Cal/Kg). T. chebula had moisture content (8.95%), lower than Indian coal (16.5%).A strong correlation (0.8226) between GCV values of bio-waste and fossil fuels was observed, highlighting the dual opportunity to address waste disposal issues and mitigate energy crises. Implementing these solutions can tackle environmental concerns while promoting sustainable development, creating value-added opportunities for traditional craft industries.